Self-Assembled Antimicrobial and biocompatible copolymer films on Titanium - Pfaffenroth, Cornelia (2011)
Biofilm formation on biomedical devices such as dental implants can result in serious infections and finally in device failure. Polymer coatings which provide antimicrobial action to surfaces without compromising the compatibility with human tissue are of great interest. Copolymers of 4-vinyl-N-hexylpyridinium bromide and dimethyl(2-methacryloyloxyethyl) phosphonate are interesting candidates in this respect. These copolymers form ultrathin polycationic layers on titanium surfaces. As the copolymerization reaction is almost ideal statistical, copolymers with varying compositions can be synthesized and immobilized onto titanium surfaces for comprehensive screening concerning antimicrobial activity and biocompatibility. Copolymer films on titanium were characterized by contact angle measurements, ellipsometry and X-ray photoelectron spectroscopy. Antibacterial properties were assessed by investigation of adherence of S. mutans which represents a strain found in the human oral cavity. Biocompatibility was rated based on human gingival fibroblast adhesion, proliferation and cell morphology. Depending on polymer composition the coatings displayed a behavior ranging from biocompatibility equal to titanium but no antibacterial action to highly antimicrobial activity but poor biocompatibility. By balancing these two opposing effects by tailoring chemical composition, copolymer coatings were fabricated, which were able to inhibit the growth of S. mutans on the surface significantly but still show a sufficient attachment of gingival fibroblasts.